How Influencer Endorsements and TikTok Advertising Shape Purchase Intentions for Glad 2 Glow Skincare Products - Irene Vanessa Ramadhani; Satria Bangsawan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study seeks to evaluate the impact of influencer endorsements and social media advertisements on consumer purchase intentions for Glad 2 Glow skincare products on TikTok. A quantitative approach was employed, using a survey method with 128 Indonesian respondents who had been exposed to influencer endorsements and social media advertisements for Glad 2 Glow on TikTok. Data were gathered through questionnaires and analyzed using a t-test to assess the direct effects of the variables on purchase intention. The criterion for acceptance was set at t-value > t-table. The results indicated that both influencer endorsements (X1) and social media advertisements (X2) significantly affect purchase intentions (Y). Influencer endorsements recorded a t-value of 3.289 with a regression coefficient of 0.266, while social media advertisements showed a t-value of 2.471 with a regression coefficient of 0.195, both surpassing the t-table value of 1.979. Consequently, hypotheses H1 and H2 were supported.